Training and Simulation "Pemulasaran Jenazah Covid-19" - Supardi Suparti; Sutaryono Sutaryono (Urecol Journal. Part F: Community Development, 2021)
Covid 19 has an impact on all lines of life, one of which is the social impact due to the curing of corpses, namely public fear, this is due to a lack of understanding of how to handle the corpse. Therefore, it is necessary to carry out socialization activities and training for cadaveric care. The purpose of this community service is to carry out socialization and training on the burial of corpses at the Trucuk Muhammadiyah Branch Manager, Klaten Regency. This community service activity method uses "Participatory Training" which is a training that prioritizes participation in the form of Socialization and Training activities related to the relocation of corpses. The activity was carried out at the AR Facrudin Building for the Trucuk Muhammadiyah Branch Manager for one day on July 26, 2020. The participants of this activity were 42 people consisting of representatives of the Muhammadiyah Branch Leadership (PCM) Trucuk, Aisiyah, PKU Assembly, NA, IPM, Muhammadiyah Youth and Institutions Disaster Management (LPB). The training resource persons consisted of elements from health institutions, religious leaders and epidemiologists. The training participants gained knowledge of the management of corpses, starting from the time the body was washed, the installation of the shroud, performing the funeral prayer, the autopsy process, to the delivery and burial of the corpse. This training also formed an agreement to create a Trucuk Branch Muhammadiyah Health Volunteer Team under LPB who is ready to help provide socialization, enlightenment and calm the community in handling the relocation of Covid 19 corpses according to health protocols. In conclusion, the implementation of socialization and training of corpse relocation can run well and smoothly. The formation of the Muhammadiyah Trucuk Health volunteer, the training participants are expected to be able to help handle the bodies of covid 19 according to health protocols correctly in their surrounding environment.